Development of some New Micronutrient Rich Blends of Edible Vegeteble Oils - Shakir Ali2, Kashif Hussain3, M. S Alam4, Anwar Habib5, Hamid Nawaz Khan1*, Jafar Salamat Khan1, (Current Botany, 2011)
Fats and oils in the form of edible vegetable oils are integral to our diets, and comprises of an important source of calorie density in human diet. Besides, the edible vegetable oils have nutritional value and health benefits due to the presence of essential fatty acids and many micronutrients as unsaponifiable matter. The unsaponifiable matter of vegetable oils includes micronutrients such as tocopherols, tocotrienols, b-carotene, oryzanol, squalene etc, which have been reported for health benefits.